Income Inequality and Regional Index of Financial Inclusion For Islamic Bank in Indonesia - Prastowo Prastowo; Diyah Putriani (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
Abstract. This research is proposed to measure financial inclusion index in 2 dimensions (2D-FII) in Indonesia Islamic banks. This research contributes to the measurement 2D-FII at the regional level in Indonesia. The analysis of cross- section data from 33 provinces in Indonesia between 2014 and 2015 shows that the value of FII in Islamic banking in Indonesia is still low. Previous works show one of the determinants on increasing inequality in any country is limited access to the financial sector, especially for low-income household (Akimov, Wijeweera, and Dollery 2006; Kenourgios and Samitas 2007; Levine 2003; D. Park and Shin 2015). Thus, the low level of FII in Indonesia perhaps is caused by inequality of income. Therefore, this research recommends policymaker to have more concern on poverty alleviation program and open new Islamic banks branches at the regional level.Keywords: 2 Dimension – Financial Inclusion Index (2D-FII), Income Inequality, Poverty Alleviation, Islamic Banks Abstrak. Penelitian ini bertujuan untuk mengukur indeks inklusi keuangan pada 2 dimensi (2D-FII) pada bank-bank syariah di Indonesia. Secara umum, penelitian ini berkontribusi pada pengukuran 2D-FII di tingkat regional Indonesia. Analisis terhadap data dari 33 provinsi di Indonesia antara tahun 2014-2015 menunjukkan bahwa nilai FII pada perbankan syariah di Indonesia masih rendah. Kajian-kajian terdahulu menunjukkan bahwa salah satu penentu peningkatan ketimpangan di berbagai negara adalah akibat akses terhadap sector keuangan yang masih terbatas, khususnya pada rumah tangga dengan pendapatan rendah (Akimov, Wijeweera, and Dollery 2006; Kenourgios and Samitas 2007; Levine 2003; D. Park and Shin 2015). Dengan begitu, rendahnya tingkat FII di Indonesia bisa jadi disebabkan oleh ketimpangan pendapatan. Oleh karena itu, penelitian merekomendasikan pengambil kebijakan untuk lebih fokus pada program pengentasan kemiskinan dan pembukaan cabang-cabang bank syariah di tingkat regional.Kata kunci: 2 Dimension – Financial Inclusion Index (2D-FII), Ketimpangan Pendapatan, Pengentasan Kemiskinan, Bank Syariah